ANALISIS YURIDIS TERHADAP PEMBERHENTIAN NADZIR WAKAF DALAM PERSPEKTIF FIQIH ISLAM DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (Studi di Kecamatan Samudera Kabupaten Aceh Utara) - MUHAMMAD EKA SYAHREL (PREMISE LAW JURNAL, 2016)
Wakaf (property donated for religious/community purposes) is one of the Islamic social institutions which has the value of ibadah (service to Allah the Almighty).The position of nazir (the person who takes care of wakaf property) is very vital since he is responsible for taking care of it and developing wakaf so that it will function properly. One of the problems of wakaf in Samudera Subdistrict is that the wakaf nazir is dismissed before his tenure ends with reasonable background for his dismissal. In consequence, he loses his right and obligation as stipulated in Law No. 41/2004 on Wakaf. The problems of the research were as follows: how about the procedure of dismissing a wakaf nazir in the perspective of the Islamic Fiqh and Law No. 41/2004 on Wakaf, how about the right and obligation of a wakaf nazir who was dismissed in the perspective of the Islamic Fiqh and Law No. 41/2004 on Wakaf, and what factor which caused a wakaf nazir to be dismissed before his tenure ended in Samudera Subdistrict, North Aceh District. The research used judicial empirical method. The procedure of dismissing a wakaf nazir in the perspective of the Islamic Fiqh and Law No. 41/2004 is regulated in Article 45 of Law No. 41/2004 and in Article 221 of KHI (Compilation of the Islamic laws). he is not reliable in taking care of the wakaf property or the wakaf management is not transparent. It is recommended that the person who will be appointed as a wakaf nazir fully understand his duty well according to the Islamic Fiqh in the KHI and in Law No. 41/2004. A wakaf nazir who manages wakaf property in each Subdistrict or village should be supervised and assessed properly so that there will no embezzlement of wakaf property. Keywords: Dismissal of Wakaf Nazir